The Jeffersonians : the visionary presidencies of Jefferson, Madison, and Monroe - Gutzman, Kevin R. C. (Kevin Raeder Constantine), 1963- (St. Martin's Press, an imprint of St. Martin's Publishing Group, 2022)
"A lively and essential chronicle of the only consecutive trio of two-term presidencies of the same political party in American history, from the bestselling author of Thomas Jefferson - Revolutionary and James Madison. Before the consecutive two-term administrations of Presidents Bill Clinton, George W. Bush, and Barack Obama, there had only been one other trio of its type: Thomas Jefferson, James Madison, and James Monroe. Kevin R. C. Gutzman's The Jeffersonians is a complete chronicle of the men, known as The Virginia Dynasty, who served as president from 1801 to 1825 and implemented the foreign policy, domestic, and constitutional agenda of the radical wing of the American Revolution, setting guideposts for later American liberals to follow. The three close political allies were tightly related: Jefferson and Madison were the closest of friends, and Monroe was Jefferson's former law student. Their achievements were many, including the founding of the opposition Republican Party in the 1790s; the Louisiana Purchase; and the call upon Congress in 1806 to use its constitutional power to ban slave imports beginning on January 1, 1808. Of course, not everything the Virginia Dynasty undertook was a success: Its chief failure might have been the ineptly planned and led War of 1812. In general, however, when Monroe rode off into the sunset in 1825, his passing and the end of The Virginia Dynasty were much lamented. Kevin R. C. Gutzman's stunning book details a time in America when three Presidents worked toward common goals to strengthen our Republic in a way we rarely see in American politics today"--